Accelerated stability and antimicrobial sensitivity studies of amoxicillin dry suspensions marketed in Bangladesh - Syed Shabbir Haider, Nishat Nasrin, Apurba Sarker Apu, Muhammad Asaduzzaman (Journal of Applied Pharmaceutical Science)
Since its introduction, amoxicillin dry suspension has been the mainstay for the antibacterial therapy for paediatric patients. But use of substandard preparation of antibiotic is one of the most important causes of microbial resistance. The present study has been carried out to evaluate the quality and stability status of 10 marketed amoxicillin dry suspensions of Bangladesh. All the brands were analyzed for their potency using chemical and microbiological methods described in the United States Pharmacopoeia and British Pharmacopoeia. Potency determination was done at three controlled temperatures - refrigerated, room and elevated (40ºC) showed that two samples were over potent but one sample was substandard out of the 10 samples. The initial potencies of the two samples were within USP range when freshly reconstituted but after 7 days, at room temperature, potencies deteriorated and came down to 90%. In refrigerated condition, all the samples remained in good condition and at 40?C, a considerable loss of potencies in all the samples were observed. Results of microbiological assay also support the results of chemical assay. The study emphasizes the necessity of routine inspection, monitoring and evaluation of quality of formulations containing amoxicillin dry syrup.
Keywords: Amoxicillin, dry suspension, paediatric patients, substandard, reconstituted.